Zakat dan Indeks Pembangunan Manusia dalam Pengentasan Kemiskinan Jawa Tengah Tahun 2019-2021 - Pangestu, Dimas Bayu; Ratno, Fernaldi Anggadha (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2024)
The aim of this research is to analyze the influence of zakat (X1), Human Development Index (X2), wages (X3), and population (X4) on poverty (Y) in Central Java province in 2019-2021. The research carried out this time used quantitative research because the approach was carried out through a process of hypothesis testing, data analysis and creating a conclusion. The data used is secondary data based on time and region which is called panel data. Data was obtained via the BPS and BAZNAS Central Java access pages and processed using E-Views 9, with tests carried out using hypothesis testing and classical assumption testing. Based on the hypothesis test obtained, each variable partially influences poverty, with the result that variable X1 has an insignificant negative effect. Variable X2 has a significant negative effect on poverty. Variable X3 has a significant positive effect. Variable X4 has a positive and significant effect.